Standar Pelayanan Administrasi Pemerintah Desa Pendem Kecamatan Junrejo Kota Batu - Adiwidjaja, Ignatius; Larasati, Dewi Citra; Abuk, Yovita (Lenvari: Journal of Social Science, 2023)
Public service is an activity or series of activities in order to meet the needs of services in accordance with laws and regulations for every citizen and resident of goods, services, and administrative services provided by the government. The purpose of this study is (a) to be able to describe the standard of administrative services of the village government of Pendem, Junrejo District, Batu City. (b) to be able to identify factors that affect the standard of administrative services of the government of Pendem Village, Junrejo District, Batu City. The data collection techniques used are observation, interviews and documentation. Based on the results of research conducted by the author, it can be concluded that administrative service standards have been running in accordance with service operational standards or (SOP), and are in accordance with applicable regulations. However, in fact, based on the results of initial observations at the research location, data was obtained that public service information at the Pendem Village office had not been fully achieved, there were inhibiting factors in services, such as low human resources, namely there were still some people who did not understand the requirements in managing correspondence